Budgeting in Austria - Blöndal, Jón R.. (OECD Publishing, 2007)
This article discusses budgeting institutions, processes and practices at the federal level in Austria. Separate sections are devoted to the budget formulation process, the role of parliament, and various aspects of budget implementation and government management issues. Each section highlights the government's reform agenda and current practices, and analyses the two vis-à-vis OECD best practices